Penetrating cardiac trauma in stab wounds: A study of diagnostic accuracy of the cardiac area (2020)
BACKGROUND: Stab wounds (SW) to the thorax raises suspicion for cardiac injuries; however, the topographic description is variable. The present study aims to evaluate different topographical descriptions within the thorax and establish their diagnostic value in penetrating cardiac trauma by SW. METHODS: Medical records of all patients admitted to our center with thoracic SW from January 2013 to June 2016 were included in this study. Diagnostic value potential was measured using different areas of the thorax described in the literature. RESULTS: In this study, we analyzed 306 cases. Thirty-eight (12.4%) patients had a cardiac injury managed surgically. Death by cardiac injury occurred in seven (18.4%) patients. The cardiac area defined between the right mid-clavicle line until the left anterior axillary line, and between 2nd and 6th intercostal spaces was the more accurate. It has sensitivity of 97.3%, specificity 72%, positive predictive value 33%, negative predictive value 99.4% and accuracy 75.1% for penetrating cardiac trauma. ROC was 0.894 IC 95% (0.760–0.901). CONCLUSION: Among the thoracic areas, topographical limits between the right mid-clavicle line and the left anterior axillary line, and between 2nd and 6th intercostal spaces are the more accurate and are highly indicative of cardiac injury in patients with SW to the thorax.